Synthesis of 3-((trifluoromethyl)thio)indoles via trifluoromethylthiolation of 2-alkynyl azidoarenes with AgSCF3 - Jongkonporn Phetcharawetch (2022)
Direct and effective trifluoromethylthiolation of 2-alkynyl azidoarenes with silver(I) trifluoromethanethiolate (AgSCF3) has been developed for the construction of 3-((trifluoromethyl)thio)indoles. The trifluoromethylthiolation protocol is compatible with a broad substrate scope, providing a variety of 3-((trifluoromethyl)thio)indoles in moderate to good yields within one step, open-air, and short reaction time.